Effects of a community-based healthy heart program on increasing healthy women's physical activity: a randomized controlled trial guided by Community-based Participatory Research (CBPR) - Seyednezami Nasrin; Nabipour Iraj; Pazoki Raha; Imami Seyed (BMC, 2007)
Abstract Background Cardiovascular disease remains the leading killer of women in most developed areas of the world. Rates of physical inactivity and poor nutrition, which are two of the most important modifiable risk factors for cardiovascular disease in women, are substantial. This study sought to examine the effectiveness of a community-based lifestyle-modification program on increasing women's physical activity in a randomized trial guided by community-based participatory research (CBPR) methods. Methods A total of 335 healthy, 25-64 years old women who had been selected by a multiple-stage stratified cluster random sampling method in Bushehr Port/I.R. Iran, were randomized into control and intervention groups. The intervention group completed an 8-week lifestyle modification program for increasing their physical activity, based on a revised form of Choose to Move program; an American Heart Association Physical Activity Program for Women. Audio-taped activity instructions with music and practical usage of the educational package were given to the intervention group in weekly home-visits by 53 volunteers from local non-governmental and community-based organizations. Results Among the participants, the percentage who reported being active (at lease 30 minutes of moderate intensity physical activity for at least 5 days a week, or at least 20 minutes of vigorous physical activity for at least three days a week) increased from 3% and 2.7% at baseline to 13.4% and 3% (p < 0.0001) at the ending of the program in the intervention and control groups, respectively. The participants in the intervention group reported more minutes of physical activity per week (mean = 139.81, SE = 23.35) than women in the control group (mean = 40.14, SE = 12.65) at week 8 (p < 0.0001). The intervention group subjects exhibited a significantly greater decrease in systolic blood pressure (-10.0 mmHg) than the control group women (+2.0. mmHg). The mean ranks for posttest healthy heart knowledge in the intervention and control groups were 198.91 and 135.77, respectively (P < 0.0001). Conclusion An intervention based on CBPR methods can be effective for the short-term adoption of physical activity behavior among women. The development of participatory process to support the adequate delivery of lifestyle-modification programs is feasible and an effective healthcare delivery strategy for cardiovascular community health promotion. Trial Registration ACTRNO12606000521527